Modern Information Technologies: Obstacles and Assistants in Management Decision-Making. Article One. Obstacles - V. A. Shamakhov; N. M. Mezhevich (Управленческое консультирование)
The dependence of management decisions on information support is not a debatable issue for a long time. However, the changing quality of information creates both new challenges and new opportunities in the information and analytical field. The decision-making process, which would seem to be facilitated by digitalization, is actually becoming more complicated. As one of the main effects of digitalization, we note the apparent availability of information. In fact, simple facts that create an information network no longer become, moreover, they become smaller, or rather, their availability decreases. The necessary information sinks in the ocean of information noise. Echo chambers and filter bubbles exacerbate this problem.